Frequency of Lower Lung Field Tuberculosis in Diabetes Mellitus Patients Attending Tertiary Care Hospital in Bangladesh: A Cross‐Sectional Study - Raihan Kamal Galib; Susanta Kumar Paul; Khujjista Akter; Manzurul Ibrahim Musa; Dip Jyoti Sarker; Shah Ashiqur Rahman Ashiq Choudhury; Shipan Chandra Paul; Rajashish Chakrabortty (Health Science Reports)
ABSTRACT Background and Aims People who have diabetes mellitus (DM) are thought to be more susceptible to pulmonary tuberculosis (PTB). Several published comparative investigations have reported that chest x‐ray images from PTB with DM are considered atypical due to their frequent involvement of the lower lung field (LLF). This study aimed to investigate the frequency of lower lung field tuberculosis (LLF‐TB) in DM and the risk factor of DM for the development of TB. Methods This study was a cross‐sectional study. PTB was diagnosed by positive sputum acid‐fast bacilli (AFB),/Culture,/Gene Xpert MTB/RIF, and DM, which was proven by taking oral hypoglycemic drugs or receiving insulin at the time of hospital admission. Extrapulmonary tuberculosis and seropositive human immunodeficiency virus (HIV) were excluded from this study. A chest x‐ray posterior‐anterior (P/A) view was done to assess the frequency and patterns of lung involvement. Logistic regression analysis was performed to evaluate the risk factor of DM for the development of TB. Results A total of 117 PTB‐DM participants were studied in this study. The mean age and frequency of isolated LLF‐TB were 53.17 ± 14.38 years and 20.5%, respectively. The prevalence of LLF‐TB and other radiological patterns were statistically significantly correlated with smear positivity (83.3% vs. 20.4%), erythrocyte sedimentation rate (ESR) > 50 mm (95.8% vs. 16.1%), and HbA1c > 7 (79.2% vs. 16.1%). Regression analysis showed that the odds ratio (OR) was 6.81 and 3.93 for DM and age (> 40 years) for the development of LLF‐TB (p < 0.05). Conclusion The frequency of LLF‐TB among PTB DM patients was around 1/5th. The development of LLF‐TB was substantially associated with DM and age greater than 40 years.